Potensi Serbuk Biji Ketumbar dan Rimpang Jahe terhadap Hama Kumbang Kacang Azuki Callosobruchus chinensis - M. Bayu Mario; Ludji Pantja Astuti; Lekhnath Kafle; Jue-Liang Hsu; Muh. Ridha Taqwa Tang; Ito Fernando; Yogo Setiawan (Jurnal Ilmu Alam dan Lingkungan, 2023)
Adzuki bean weevil, Callosobruchus chinensis (Linnaeus) (Coleoptera: Chrysomelidae) is one of primary pests that infest the adzuki bean, mung bean, cowpea, chickpea, and other legumes. This study aimed to investigate the effect of coriander seed and ginger rhizome powders in 1, 2, and 3 g dose admixed directly with adzuki bean on biological variables of C. chinensis and grain quality in laboratory conditions. This study was arranged by completely randomized design (CRD) that consisted of six combination treatments and control. Each of treatment was repeated five times. Observed biological variables consisted of adult longevity, fecundity, and F1 progeny. Observed grain quality variables consisted of percentage of damaged grain and grain viability. Results showed that adzuki bean treated with ginger powder on 2 and 3 g dose had good results to control C. chinensis and kept the grain quality in relatively good condition compared to other treatments and control.